Carbohydrate Mouth Rinse Decreases Time to Complete a Simulated Cycling Time Trial - Baltazar-Martins, Gabriel; Del Coso, Juan (Frontiers in Nutrition, 2019)
Rinsing carbohydrate solutions in the mouth can produce positive effects on the central nervous system via mouth/tongue receptors, ultimately increasing cycling performance. However, previous investigations on this topic have used complex carbohydrate solutions and time trials on a cyclergometer to complete a set amount of work. The purpose of the present study was to examine the effects of carbohydrate mouth rinsing on physical performance by using a commercially available drink during a simulated cycling competition with varying slopes. In a double-blind, placebo-controlled and randomized manner, 16 well-trained cyclists (37.6 ± 3.5 years; 76.9 ± 7.9 kg) performed two simulated cycling competitions (25.3 km) with their own bikes on a 3D virtual trainer. In one occasion, participants mouth-rinsed a 6.4% carbohydrate mixed solution for 5 seconds each 12.5% of total completion of the trial; in other occasion participants rinsed with a taste-matched placebo with 0.0% of carbohydrate. During the trials, participants were instructed to perform as fast as possible at a self-chosen pace while time, cycling power output and ratings of perceived exertion were obtained during the trials. When compared to the placebo, carbohydrate mouth rinse decreased the time employed to complete the simulated competition (2960 ± 412 vs 2888 ± 396 s; P = 0.04, respectively), while it increased overall cycling power (222 ± 51 vs. 231 ± 46 w, P = 0.04) and cycling power during the climbing sections (238 ± 46 vs. 248 ± 47 w, P = 0.03). Carbohydrate mouth rinse also increased the rating of perceived exertion at the end of the competition (18.3 ± 1.7 vs. 18.9 ± 1.1 arbitrary units, P = 0.04). In summary, mouth rinsing with a commercially available carbohydrate drink might be considered as an effective strategy to increase physical performance during cycling competition.